Characterization of a New Lignocellulosic Fiber from Brazil: Imperata brasiliensis (Brazilian Satintail) as an Alternative Source for Nanocellulose Extraction - Coelho de Carvalho Benini, Kelly Cristina [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Cioffi, Maria Odila Hilário [UNESP]; Milanese, Andressa Cecília [UNESP]; Ornaghi, Heitor L. (Taylor & Francis, 2017)
The chemical, physical and thermal properties of a new lignocellulosic fiber from Brazil (Imperata brasiliensis) were examined by SEM, chemical composition, XRD, FTIR, and TGA. Fibers were analyzed aiming to compare the properties of its new natural resource with other lignocellulosic fibers used as a source of nanocellulose extraction. Microscopy analysis demonstrated that the bundle of fibers presented a variety of size and shapes, ranging between 25 and 500 µm, while a single fiber has a diameter of 5 µm. The chemical composition showed the presence of 37.7% of cellulose, 35% of hemicellulose and 14.3% of lignin. The total crystallinity index (CI) calculated using Segal method was of 36.6%. By TGA, it was possible to identify the degradation step of each primary component of lignocellulosic fiber and to observe that the onset degradation temperature was 157°C. With the results of ATR-FTIR technique, it was possible to estimate the CI, and the results exhibited good agreement with that calculated by XRD. Finally it was possible to conclude that fibers obtained from Imperata brasiliensis are suitable to be used as a resource for nanocellulose obtainment since presents almost the same properties of other lignocellulosic fibers successfully used in literature for nanocellulose extraction.
Keywords: ATR-FTIR; Brazilian satintail; Imperata brasiliensis fibers; microscopy analysis; thermal analysis; X-ray analysis